2017
DOI: 10.14411/fp.2017.034
|View full text |Cite
|
Sign up to set email alerts
|

Stray cats are more frequently infected with zoonotic protists than pet cats

Abstract: Faecal samples were collected from cats kept as pets (n = 120) and stray cats (n = 135) in Central Europe (Czech Republic, Poland and Slovakia) and screened for the presence of Cryptosporidium spp., Giardia intestinalis (Kunstler, 1882), Encephalitozoon spp. and Enterocytozoon bieneusi Desportes, Le Charpentier, Galian, Bernard, Cochand-Priollet, Lavergne, Ravisse et Modigliani, 1985 by PCR analysis of the small-subunit of rRNA (Cryptosporidium spp. and G. intestinalis) and ITS (microsporidia) genes. Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
6
20
2
Order By: Relevance
“…Our sequencing data analysis revealed the presence of three known genotypes: D, EbpC and Type IV. This is in concordance with observations from some earlier studies in Brazil, Turkey, Japan, Thailand, Colombia, Germany, Portugal, Slovakia and China [7,8,12,15,16,20,21,23,[26][27][28]. Genotypes D, EbpC, and Type IV are known to have a broad-host range and have been reported in nonhuman primates, dogs, cats and domestic animals, and even in wastewater [12,15,[29][30][31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our sequencing data analysis revealed the presence of three known genotypes: D, EbpC and Type IV. This is in concordance with observations from some earlier studies in Brazil, Turkey, Japan, Thailand, Colombia, Germany, Portugal, Slovakia and China [7,8,12,15,16,20,21,23,[26][27][28]. Genotypes D, EbpC, and Type IV are known to have a broad-host range and have been reported in nonhuman primates, dogs, cats and domestic animals, and even in wastewater [12,15,[29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…A high degree of genetic diversity in E. bieneusi was observed in dogs (PtEb IX, GD1 to GD6, D, CD9, EbpC, I) and cats (PtEb IX, GD1 to GD2, D, CD9, EbpC, Type IV, GC1) in the present study; these findings show similarity with some studies in Heilongjiang, Henan and Anhui provinces, China [12,14,15]. In contrast, low genetic heterogeneity in E. bieneusi was observed in dogs and cats in other studies with only genotypes PtEb IX and D found in dogs and genotypes Type IV and D in cats in Shanghai city, China [16], only one genotype, PtEb IX, in dogs in Japan [24], and one genotype, D, in cats in Slovakia, Poland, and the Czech Republic [21]. As with most previous reports [10,12,[14][15][16]24], we identified genotype PtEbIX as dominant in dogs and cats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A high degree of genetic diversity in E. bieneusi was observed in dogs (PtEb IX, GD1 to GD6, D, CD9, EbpC, I) and cats (PtEb IX, GD1 to GD2, D, CD9, EbpC, Type IV, GC1) in the present study; these ndings show similarity with some studies in Heilongjiang, Henan and Anhui provinces, China [12,14,15]. In contrast, low genetic heterogeneity in E. bieneusi was observed in dogs and cats in other studies with only genotypes PtEb IX and D found in dogs and genotypes Type IV and D in cats in Shanghai city, China [16], only one genotype, PtEb IX, in dogs in Japan [24], and one genotype, D, in cats in Slovakia, Poland, and the Czech Republic [21]. As with most previous reports [10,12,[14][15][16]24], we identi ed genotype PtEbIX as dominant in dogs and cats.…”
Section: Discussionmentioning
confidence: 96%
“…Infections with E. bieneusi in dogs and cats have been reported in Spain, Brazil, China, Colombia, Germany, Japan, Portugal, Switzerland, Poland, Turkey, Iran, the Czech Republic, Egypt, and Thailand, where they range from 0% to 25.8% in dogs and from 1.4% to 31.3% in cats [7,9,[14][15][16][18][19][20][21][22][23]. In the present study, 149 dogs (22.9%) and 79 cats (20.3%) were E. bieneusi-positive by nested PCR-based sequencing of the ITS region, a somewhat higher rate than those reported in most previous studies.…”
Section: Discussionmentioning
confidence: 99%